Pengaruh SMM terhadap Pembelian Tidak Terencana Dimediasi Perilaku FoMO pada Aroma Baking - Nabil, Adiva; Sutomo, Maskuri; Ponirin, Ponirin; Auriza, Mohammad Zeylo (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to examine the effect of social media marketing on unplanned purchases, with FoMO behavior as a mediating factor, at Aroma Baking. Research methodology: This research uses a quantitative approach with a survey design, with a sample of 105 respondents. The sample was determined using a purposive sampling technique. The data were statistically analyzed using the SEM-PLS method using Smart PLS 4.1. Result: This study demonstrates that social media marketing significantly influences unplanned purchases (? = 0.672, p = 0.000) and FoMO behavior (? = 0.954, p = 0.000). FoMO behavior also significantly affects unplanned purchases (? = 0.317, p = 0.000) and mediates the relationship between social media marketing and unplanned purchases (? = 0.303, p = 0.000). Conclusion: This study shows that social media marketing has a positive and significant effect on unplanned purchases, both directly and through the mediation of FoMO behavior. FoMO is shown to strengthen the relationship between social media marketing and consumers' impulse to buy spontaneously on Aroma Baking products. Limitations: This research has limitations that need to be considered, namely the object of research is only focused on one UMKM, namely Aroma Baking in Palu City, so that the findings cannot be generalized to similar businesses in other regions or sectors. For this reason, the suggestions in this study are, for companies to examine whether certain age groups or segments are more prone to FoMO and impulse buying, so that marketing strategies can be more targeted. Contribution: The findings can be useful as a practical reference for local businesses in Palu and surrounding areas in developing more effective social media-based marketing strategies.